Laser-induced breakdown spectroscopy (LIBS) in biomedical analysis - Zhang, Rongling; Hu, Shunfan; Ma, Changfei; Zhang, Tianlong; Li, Hua (TrAC, Trends in analytical chemistry (Regular ed.), 2024)
The subtle changes in elements within a biological system can directly impact metabolism and physiological processes. Rapid and accurate analysis of elements in the body is essential for clinical disease diagnosis. Laser-induced breakdown spectroscopy (LIBS) has been widely used because it is rapid, in-situ, and micro-damage. This review summarizes the research status of LIBS in biomedical analysis in 2017–2024. The basic research of LIBS is introduced initially. Based on the different research subjects, biomedical applications of LIBS are divided into three categories, namely, microorganisms, biological tissues, and medicinal plants. LIBS plays a crucial role in enhancing the accuracy of pathogen identification in microorganisms. In biological tissues, it reveals elemental compositions that are vital for physiological analysis and pathological diagnosis. For medicinal plants, it focuses on the detection of heavy metals and adulteration to ensure safety and authenticity of medicines. Finally, the future prospects of LIBS in biomedicine are discussed. •The application advance and future prospects of LIBS in biomedicine are summarized.•The advantages of LIBS combined with chemometrics in biomedicine are discussed.•The relevant tactics for enhancing LIBS analytical performance are also presented.